Pemberdayaan Keluarga Sebagai Pencegahan Demensia pada Lansia - Sa’diyah, Halimatus; Indarwati, Retno; Sari, Dianis Wulan (Journal of Telenursing (JOTING), 2024)
This study aims to see how the relationship between family empowerment and efforts to prevent dementia behavior in the elderly. The method used was a systematic review of three databases; Scopus, PubMed, and Web of Science using various combinations of keywords related to "family empowerment", "dementia prevention", and "elderly" (including synonyms). Inclusion criteria were studies published between 2019 and 2024, available in English. The review process involved title and abstract screening and full-text review of potential studies. The results showed that 9 articles conveyed the support provided by families for dementia prevention consisting of several aspects, namely disease management, emotional support, physical support, lifestyle, nutritional management by consuming healthy foods, stress management, social support and financial support. In conclusion, family empowerment has a positive impact on preventing dementia in the elderly, the family provides several aspects of support received by the elderly so that it can affect cognitive conditions and prevent dementia in the elderly. Keywords: Dementia; Elderly; Family empowerment; Prevention